"Isolated" postinfectious myoclonus. Issue 11 (November 1992) - Bhatia, K; Thompson, P D; Marsden, C D
Abstract : Two cases are reported who developed myoclonus as the only manifestation of a post-infectious syndrome without evidence of encephalitis or the opsoclonus-myoclonus syndrome. Case 1 had generalised myoclonus following an influenza-like illness, while case 2 had right upper limb segmental myoclonus following uncomplicated chicken pox. Neither had any localising neurological signs or abnormality on investigation. Both recovered completely within six months of the onset. Similar cases are reviewed from the literature and it is suggested that such cases be called "isolated" post-infectious myoclonus.